Indonesian Millennials' Financial Behavior in Responding to the Cost of Hajj - Aulia, Sulthonul; Mubarak, Darihan (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This research explores how Indonesian millennials are responding to the significant costs of the Hajj pilgrimage and the financial strategies they employ to save up. The average waiting period for Hajj in Indonesia stretches to a prolonged 24 years, and this is made even more challenging by the increasing age of those currently registered, which effectively lengthens the wait time for younger, prospective pilgrims. This situation, combined with anticipated increases in historical costs and financial hurdles, may make it more challenging for future pilgrims to pay the initial deposit, potentially leading to even higher Hajj expenses in the future. Using a qualitative approach with thematic analysis, the study gathered primary data through semi-structured interviews with 11 Indonesian millennials. The findings reveal that all respondents find the total Hajj costs excessive, with the initial deposit presenting an opportunity cost for those earning below the minimum wage. A common trend, especially among low- to middle-income groups, is a preference for gold as an investment. High-income respondents are more proactive, aiming to cover the initial Hajj deposit in under five years by dedicating 10-15% of their income to specific Hajj savings. However, various financial obstacles prevent most respondents from achieving their financial goals for the Hajj pilgrimage. This study contributes to the development of a more inclusive and adaptive Hajj financial policy to the financial needs and behavior of the millennial generation in Indonesia.